2021
DOI: 10.1096/fj.202101448r
|View full text |Cite
|
Sign up to set email alerts
|

GBP5 promotes liver injury and inflammation by inducing hepatocyte apoptosis

Abstract: Liver injury is the first step in causing fibrosis, cirrhosis, and liver cancer, leading to mortality. However, the drivers of progressive liver injury are still incompletely defined. Here, we identify GBP5 as a major factor causing liver injury and inflammation. We show that the expression of GBP5 is abnormally elevated in the damaged liver, and its expression depends at least partially on the NF‐κB‐inducing kinase (NIK)/NF‐κB2 signaling pathway. Knockout of Gbp5 ameliorates D‐galactosamine/lipopolysaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…TNF protein superfamily members, including TNF-a, Fas cell surface death receptor ligand (FASL), and TNF-associated apoptosis-inducing ligand (TRAIL), are the main inducers of hepatocyte death. The TNF-a/tumor necrosis factor receptor (TNFR1), FAS/FASL, and TRAIL/TRAILR pathways can activate CASP8 and then initiate a proteolytic cascade that involves CASP3, CASP6, and CASP7, which ultimately leads to hepatocyte apoptosis [ 24 , 25 , 26 ]. We showed that TRAILR, FAS, CASP8, and CASP3 were upregulated in the LPS-stimulated piglet livers, and that the predicted lncRNA target genes were also enriched in the apoptosis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…TNF protein superfamily members, including TNF-a, Fas cell surface death receptor ligand (FASL), and TNF-associated apoptosis-inducing ligand (TRAIL), are the main inducers of hepatocyte death. The TNF-a/tumor necrosis factor receptor (TNFR1), FAS/FASL, and TRAIL/TRAILR pathways can activate CASP8 and then initiate a proteolytic cascade that involves CASP3, CASP6, and CASP7, which ultimately leads to hepatocyte apoptosis [ 24 , 25 , 26 ]. We showed that TRAILR, FAS, CASP8, and CASP3 were upregulated in the LPS-stimulated piglet livers, and that the predicted lncRNA target genes were also enriched in the apoptosis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the NLRP3 inflammasome requires two stages: Hepatic inflammatory responses co-occur with all of the liver diseases and were assumed to be involved in the onset and progression of hepatic lesions [27]. Innate immune cell activation and multiple pro-inflammatory cytokines, including TNF-α and IL-6, trigger and amplify the inflammatory hepatic damage [28]. In the current study, the LPS upregulated the pro-inflammatory mediators TNF-α, IL-6, and IL-22, which were reversed by thymol.…”
Section: Discussionmentioning
confidence: 99%
“…23 , 35 , 36 Previous research has shown that inflammatory responses, oxidative stress, endoplasmic reticulum (ER) stress, and apoptosis mainly contributed to LPS/D-GalN-induced ALF. 30 , 37 , 38 , 39 , 40 However, Liu et al 41 and Yang et al 42 found that pyroptosis occurred in LPS/D-GalN-induced ALF through activating caspase 1 and inflammasome NLR family pyrin domain containing 3 (NLRP3). Studies also showed that ferroptosis took place in LPS/D-GalN-induced ALF by increasing lipid peroxidation with cyclooxygenase (COX) and lysyl oxidase (LOX) pathway up-regulation and inhibiting GSH synthesis.…”
Section: Discussionmentioning
confidence: 99%